Price Policy and Taxation as Effective Strategies for Tobacco Control - Felsinger, Richard; Groman, Ernest (Frontiers in Public Health, 2022)
Objective: Only 13% of the world’s population are living in countries imposing appropriate tobacco tax-rates. This study aims to promote the implementation of price policy measures as a striking tobacco control strategy in Austria and to encourage other countries to further increase their taxes to WHO best-practice levels. Method: This study used the yearly economic data from Austria from 1997 to 2015. Applying a model for regression analysis, the price elasticity of total tobacco consumption was estimated. Results: Between 1997 and 2015 the price elasticity of demand for tobacco products (including cigarettes, cigars and other tobaccos) was -0,661, however, the result is statistically insignificant. When excluding two anomalous years and removing a variable of the regression model the elasticity was -0,691 and statistically significant, indicating that a one percent increase in tobacco prices will result in a 0,691% decrease of tobacco consumption. Conclusion: The responsiveness of Austrian smokers to price changes has increased during the last decades. Because other activities showed no significance in the analysis, this study should encourage countries world-wide to use price policy and taxation more intensively in order to reduce smoking rates effectively.